STRATEGI EFEKTIF UNTUK MENCEGAH BULLYING DI LINGKUNGAN SEKOLAH - Alfini Liansi; Zhyka Tirta Wardani Wardani; Mustakim Mustakim (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Bullying is a serious problem that frequently occurs in schools and negatively impacts students' psychological, social, and academic development. To address this issue, Madako University Tolitoli Community Service (KKN) students implemented a community service program entitled "Effective Strategies to Prevent Bullying in Schools" at a partner school in Tolitoli Regency. This activity aims to increase students' understanding of the forms of bullying, triggers, consequences for both victims and perpetrators, and preventive measures that can be implemented in everyday school life. Implementation methods included interactive outreach, group discussions, case simulations, educational video screenings, and the distribution of anti-bullying posters as a campaign medium. A total of 65 students were actively involved in the activity and provided positive responses. Evaluation results showed that 90% of participants experienced increased knowledge about the dangers of bullying, while others stated that this activity strengthened their ability to recognize and prevent intimidating behavior. This community service program has proven effective in fostering empathy, increasing student awareness, and encouraging the creation of a safe, inclusive, and bullying-free school environment. Thus, this activity makes a real contribution to supporting efforts to prevent violence in schools through an educational and participatory approach.